1972
DOI: 10.1172/jci107091
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Reperfusion

Abstract: A B S T R A C T The question of whether or not the size of an area of myocardial infarction, measured at 1 wk after coronary occlusion, can be influenced by coronary artery reperfusion was examined in dogs. In seven control experiments the anterior descending coronary artery was ligated, while in seven other studies the occlusion was released after 3 hr. In all animals calibrated photographs were used to assess the zone of hypoperfusion and the acutely injured area of epicardial ST segment elevation, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Reperfusion has been shown to protect ischemic myocardium from necrosis even when it is delayed for 6 hr (16,17). However, with prolonged myocardial ischemia, hemorrhagic infarcts may occur (18) and postreperfusion mechanical dysfunction, which may persist for prolonged periods, occurs (19).…”
Section: Methodsmentioning
confidence: 99%
“…Reperfusion has been shown to protect ischemic myocardium from necrosis even when it is delayed for 6 hr (16,17). However, with prolonged myocardial ischemia, hemorrhagic infarcts may occur (18) and postreperfusion mechanical dysfunction, which may persist for prolonged periods, occurs (19).…”
Section: Methodsmentioning
confidence: 99%
“…Although today it is unequivocally clear that timely reperfusion of an occluded coronary artery is the only way to rescue myocardium from impending infarction, this notion is a little more than 40 years old and goes back to the study by Ross and collaborators 39,40 who first reported that reperfusion after 180-minute coronary occlusion reduced infarct size in dogs. These findings were quickly translated to humans with acute myocardial infarction who were reperfused by thrombolysis or percutaneous coronary interventions (PCIs).…”
Section: Coronary Circulation As a Determinant Of Reperfusion And Repmentioning
confidence: 99%
“…The preservation of ischemic myocardium by early revascularization in animal models is a controversial issue (10)(11)(12)(13)(14)(15)(16)(17). Variability in experimental results may be due to many factors, including differences in collateral flow within (18) and between…”
Section: Resultsmentioning
confidence: 99%
“…The duration of coronary occlusion, after which reperfusion results in salvage of ischemic myocardium, seems to be species related. In dogs, reperfusion as early as 3 h resulted in a decrease of ultimate infarction in the majority of reports (10)(11)(12)(13)(14), but revascularization after 5 h or later produced either extension of infarction by hemorrhage (15) or no significant change in infarct size (13)(14)(15). Collateral circulation in pigs is less extensive than in dogs (19), and an equivalent coronary occlusion producing primarily a subendocardial infarction in the dog, results in a transmural infarct in the pig (20).…”
Section: Discussionmentioning
confidence: 99%